PEMBADANAN (EMBODYING) KEBIJAKAN BERBASIS KAPASITAS DALAM PEMBERDAYAAN DIFABEL UNTUK PENANGGULANGAN KEMISKINAN - Andina Elok Maharani; Isharyanto Isharyanto; Rosita Candrakirana (Jurnal Dinamika Hukum, 2014)
This empirical law research is aimed at embodying the capacity-based policy to the difable. The instrument for data’s collection was conducted by structured interview and observation which were supported by literature data. Capacity-based Approach is a model that recognizes disability based on the value of ability and function. This approach provides a framework for learning disability, particularly analyzing the defects of existing paradigms and assessing economic sources along with the disability consequences. The key point of operational level on Capacity-based Approach to the empowerment of the disable in poverty prevention includes four points: Inclusion, Participation, Access, and Quality. This study suggests a holistic approach to reform the policy to empower the disable to be free from poverty.  Key words: embodying, difable, poverty alleviation